Cost-effectiveness of a high-intensity rapid access outpatient stroke rehabilitation program. Issue 1 (March 2019) - Tam, Alan; Mac, Stephen; Isaranuwatchai, Wanrudee; Bayley, Mark
Abstract : A common strategy to improve cost-effectiveness in healthcare is to offer outpatient care instead of in-hospital care. Toronto Rehabilitation Institute developed an outpatient high-intensity fast-track (FT) stroke rehabilitation program aimed at discharging inpatient stroke rehabilitation patients earlier or bypassing inpatient rehabilitation altogether. This cost-effectiveness analysis compares FT rehabilitation within 1 week of discharge with no FT in a single healthcare payer system. Patient costs and outcomes over a 12-week time horizon were included. Using individual-level FT data from April 2015 to March 2016, incremental cost-effectiveness ratios (ICERs) (with 95% confidence interval) were estimated using regression. Subgroup analysis was completed for patients entering FT directly from inpatient rehabilitation and acute stroke care. Uncertainty was assessed using a cost-effectiveness acceptability curve with a range of willingness-to-pay values ($0–1000 per inpatient day saved). ICER (95% confidence interval) estimate for patients entering FT from inpatient rehabilitation was $404 ($270–620) per inpatient day saved. ICER estimate for direct from acute care admissions was $37 ($20–55) per day saved. At willingness-to-pay of $698 (cost of one alternate level of care day in acute care awaiting rehabilitation), the probability of FT being cost-effective was 99.2 and 100% for patients from inpatient rehabilitation and acute stroke care, respectively. From a single healthcare payer perspective, FT is a cost-effective method of providing appropriate rehabilitation intensity for stroke patients early on, and likely to provide savings to the healthcare system upstream through fewer days awaiting rehabilitation admission.